A Systematic Review Of Knowledge, Attitudes, And Prevention Strategies Related To Adolescent Substance Abuse (2016–2024) - Smriti Paul , Dr. Venice Mariya David (South Eastern European Journal of Public Health, 2025)
Adolescence is a critical period marked by physiological and psychological changes that increase vulnerability to risky behaviours, including substance abuse. This literature review synthesizes studies from 2016 to 2024 on adolescents’ knowledge, attitudes, and preventive strategies related to substance use. Findings reveal that while awareness of harmful effects exists, peer influence, media exposure, and poor mental health often promote use. Effective prevention requires integrated approaches, including school programs, family involvement, mental health services, and media regulation. Policy implementation, especially in India, remains inconsistent despite strong legal frameworks.